A comparative study of the fecal microbiota of gray seal pups and yearlings ‐ a marine mammal sentinel species. Issue 3 (23rd May 2022) - Watkins, Craig A.; Gaines, Taylor; Strathdee, Fiona; Baily, Johanna L.; Watson, Eleanor; Hall, Ailsa J.; Free, Andrew; Dagleish, Mark P.
Abstract: Gray seals ( Halichoerus grypus ) can act as sentinel species reflecting the condition of the environment they inhabit. Our previous research identified strains of pathogenic Campylobacter and Salmonella, originating from both human and agricultural animal hosts, on rectal swabs from live gray seal ( H. grypus ) pups and yearlings on the Isle of May, Scotland, UK. We examined rectal swabs from the same pup ( n  = 90) and yearling ( n  = 19) gray seals to gain further understanding into the effects of age‐related changes (pup vs. yearling) and three different natal terrestrial habitats on seal pup fecal microbiota. DNA was extracted from a subset of rectal swabs (pups n  = 23, yearlings n  = 9) using an optimized procedure, and the V4 region of the 16S ribosomal RNA gene was sequenced to identify each individual's microbiota. Diversity in pup samples was lower (3.92 ± 0.19) than yearlings (4.66 ± 0.39) although not significant at the p  = 0.05 level ( p  = 0.062) but differences in the composition of the microbiota were ( p  < 0.001). Similarly, differences between the composition of the microbiota from pups from three different terrestrial habitats (Pilgrim's Haven [PH], Rona Rocks [RR], and Tarbet Slope [TS]) were highly significant ( p  < 0.001). Pairwise tests showed significant differences between all three habitats: PH versus TS ( p  = 0.019), PH versus RR ( p  = 0.042) and TS versus RR ( p  = 0.020). This preliminary study suggests a general trend, that seal microbiomes are modified by both age and, in pups, different terrestrial habitats. Furthermore, knowledge of the microbiota species present has the potential to be used in determining the environmental quality index. Abstract : Gray seals ( Halichoerus grypus ) can act as sentinel species reflecting the condition of the environment they inhabit. We examined rectal swabs from the pups and yearling gray seals to gain further understanding into the effects of age‐related changes and three different natal terrestrial habitats on seal pup fecal microbiota. This preliminary study suggests a general trend, that seal microbiomes are modified by both age and, in pups, different terrestrial habitats. Furthermore, knowledge of the microbiota species present has the potential to be used in determining the environmental quality index.